2010
DOI: 10.1260/1369-4332.13.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Long-Term Performance of FRP Composites and FRP-Concrete Interface

Abstract: This paper presents recent developments in long-term behavior of fiber reinforced polymer (FRP) composites and FRP-strengthened concrete beams with special emphasis on the FRP-concrete interface subjected to creep and fatigue loads. Although short-term behavior of FRP-strengthened structures is intensively reported thus far, their long-term performance has not been thoroughly elucidated yet. This state-of-the-art paper provides a synthesis of recent findings on the long-term performance of FRP composites and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Further information on the technique and analysis of rehabilitating RC bridge structures using FRP composites to reinforced concrete may be obtained from Hollaway and Leeming (1999), Teng et al (2002Teng et al ( , 2004, oehlers and Seracino (2004) Hewson (2008), Forde (2009) and Hollaway and Chen (2009) and Wu et al (2010). 16.6.2 The rehabilitation of PC bridge beams in flexure using unstressed FRP plates Shanafelt and Horn (1980) reported that approximately 160 PC bridge overheight impacts were reported each year by transportation departments in the United States. Impact damage to PC girders can range from simple scrapes to large section loss and severed prestressing strands.…”
Section: 6mentioning
confidence: 99%
“…Further information on the technique and analysis of rehabilitating RC bridge structures using FRP composites to reinforced concrete may be obtained from Hollaway and Leeming (1999), Teng et al (2002Teng et al ( , 2004, oehlers and Seracino (2004) Hewson (2008), Forde (2009) and Hollaway and Chen (2009) and Wu et al (2010). 16.6.2 The rehabilitation of PC bridge beams in flexure using unstressed FRP plates Shanafelt and Horn (1980) reported that approximately 160 PC bridge overheight impacts were reported each year by transportation departments in the United States. Impact damage to PC girders can range from simple scrapes to large section loss and severed prestressing strands.…”
Section: 6mentioning
confidence: 99%
“…Since advanced fiber-reinforced polymer (FRP) composite materials have superior physical and mechanical properties, they have been widely used in civil engineering, chemical, automotive, aerospace, and other fields (Bakis et al, 2002; Bank, 2006; Canning and Luke, 2010; Smith and Teng, 2003). Anecdotal evidence provides substantial reason to believe that if appropriately designed and fabricated, these systems can provide longer lifetimes and lower maintenance costs than equivalent structures fabricated from conventional materials (Karbhari, 2003; Wu et al, 2010). However, owing to the limitations of the FRP component size and the requirements of transportation and assembling, connections between FRP structural components are inevitable (Keller, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber is light in weight, high in tensile strength and modulus of elasticity, but low in elongation and expensive. Glass fiber has high elongation and low price [1][2] . Ultimately, this new composite can combine the strength and toughness of carbon and glass fibers, avoiding the high cost of carbon fiber and the high quality of glass fiber.…”
Section: Introductionmentioning
confidence: 99%